2000
DOI: 10.1055/s-2000-7553
|View full text |Cite
|
Sign up to set email alerts
|

Management of Alcohol Withdrawal in Microvascular Head and Neck Reconstruction

Abstract: Alcohol use is a risk factor for head and neck cancer. One of the primary therapeutic modalities is surgical tumor ablation followed by immediate reconstruction. Such therapy places patients in a controlled environment, without alcohol, creating the risk of alcohol withdrawal syndrome. The authors attempted to identify the incidence of alcohol withdrawal among patients undergoing free-flap reconstruction for head and neck cancer and were interested in the effect of alcohol withdrawal on the postoperative cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The detrimental postoperative effects of chronic alcohol abuse, and specifically AWS, can potentially be lessened through abstinence from alcohol or prophylaxis against and/or proactive treatment of the symptoms directly related to the withdrawal process 1, 15, 25. Abstinence from alcohol for 4 weeks may reduce postoperative morbidity,29 and prophylactic treatment may prevent complications in patients at risk for AWS 14. Bertrand et al6 reported that preoperative nursing interventions aimed at reducing alcohol intake and the initiation of proactive prophylaxis decreased the rate of AWS in otolaryngology patients from 66% to 28%, with a reduction in intensive care unit (ICU) utilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detrimental postoperative effects of chronic alcohol abuse, and specifically AWS, can potentially be lessened through abstinence from alcohol or prophylaxis against and/or proactive treatment of the symptoms directly related to the withdrawal process 1, 15, 25. Abstinence from alcohol for 4 weeks may reduce postoperative morbidity,29 and prophylactic treatment may prevent complications in patients at risk for AWS 14. Bertrand et al6 reported that preoperative nursing interventions aimed at reducing alcohol intake and the initiation of proactive prophylaxis decreased the rate of AWS in otolaryngology patients from 66% to 28%, with a reduction in intensive care unit (ICU) utilization.…”
Section: Discussionmentioning
confidence: 99%
“…As many as 66% to 82% of patients who chronically abuse alcohol develop alcohol withdrawal symptoms (AWS) of autonomic hyperactivity with cessation of use following surgery and may subsequently experience postoperative complication rates as high as 50% to 55% 6, 9, 13. Preoperative abstinence and benzodiazepine prophylaxis have been shown to decrease the incidence of AWS in patients at risk and is associated with a decrease in postoperative complications, but does not prevent AWS in all patients at risk 9, 14, 15. Limited data exist regarding the effects of alcohol abuse and alcohol withdrawal on outcomes and costs of care in HNCA surgical patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the severity and type of postoperative complications appears to differ between patients undergoing surgery for head and neck cancer who develop alcohol withdrawal symptoms compared with patients who do not develop withdrawal. Weinfeld et al 2 found a statistically significant difference in the ratio of nonsite‐related to site‐related complications in patients with AWS compared with those without symptoms of alcohol withdrawal. The majority of complications in their patients with AWS were systemic (75%), and all were classified as major.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients become physiologically dependent on the central nervous inhibitory effects of alcohol after prolonged use. Consequently, patients may develop symptoms of autonomic hyperactivity such as tachycardia, diaphoresis, hyperthermia, and hypertension as a result of withheld consumption during hospitalization after surgical resection 2 …”
Section: Introductionmentioning
confidence: 99%